Investigation of fouling mechanisms of virus filters during the filtration of protein solutions using a high throughput filtration screening device. (26th April 2019) - Bieberbach, Marc; Kosiol, Peter; Seay, Alexander; Bennecke, Moritz; Hansmann, Björn; Hepbildikler, Stefan; Thom, Volkmar
Abstract : The downstream process development of novel antibodies (Abs) is often challenged by virus filter fouling making a better understanding of the underlying mechanisms highly desirable. The present study combines the protein characterization of different feedstreams with their virus filtration performance using a novel high throughput filtration screening system. Filtration experiments with Ab concentrations of up to 20 g/L using either low interacting or hydrophobically interacting pre‐filters indicate the existence of two different fouling mechanisms, an irreversible and a reversible one. At the molecular level, size exclusion chromatography revealed that the presence of large amount of high molecular weight species—considered as irreversible aggregates—correlates with irreversible fouling that caused reduced Ab throughput. Results using dynamic light scattering show that a concentration dependent increase of the mean hydrodynamic diameter to the range of dimers (17 nm at 20 g/L) together with a negative DLS interaction parameter k D (−18 mL/g) correlate with the propensity to form reversible aggregates and to cause reversible fouling, probably by a decelerated Ab transport velocity within the virus filter. The two fouling mechanisms are further supported by buffer flush experiments. Finally, concepts for reversible and irreversible fouling mechanisms are discussed together with strategies for respective fouling mitigation. © 2019 American Institute of Chemical Engineers Biotechnol. Prog., 35: e2776, 2019.